Local and systemic factors both required for full renewal of deer antlers, and systemic factors only for generic cutaneous regenerative healing - Wenying Wang; Qianqian Guo; Chunyi Li (Cell Regeneration)
Abstract Deer antlers are the only mammalian organs that periodically regenerate from permanent bony protuberances (pedicles). Antler regeneration relies on the presence of pedicle periosteum (PP) and starts from regenerative healing of wounds created following the hard antler casting. Interestingly, PP deletion (removal of local factors) abolishes antler regeneration and the transition to velvet skin (shiny and hair sparsely populated) but cannot inhibit regenerative wound healing although the healed tissue is of pedicle type (scalp-like); this indicates that systemic factors from circulating blood contribute to the generic regenerative wound healing. Subsequently, we created full-thickness excisional (FTE) skin wounds on the forehead region in sika deer. Different healing outcomes ensued, namely regeneration or formation of a scar, depending on whether the intervention took place during the period of antler regeneration (ARP; spring–summer) or in the period where antler regeneration does not occur (non-ARP; winter). Forehead wounds during ARP exhibited regenerative healing, whereas during the non-ARP, healing took place but with a scar. Therefore, systemic factors from the circulating blood during the ARP must be responsible for this outcome. Topical application of deer blood plasma (a source of systemic factors) from ARP to FTE wounds in rats promoted regenerative healing, whereas, that from non-ARP failed to do so. Further evaluation showed that regenerative healing was achieved through increased cell proliferation, impaired inflammatory response, reduced myofibroblast transformation, and orchestrated collagen remodeling accompanied by an increase in the ratio of TGF-β3 to TGF-β1. Comparative proteomics analysis of deer plasma identified some highly up-regulated factors from the plasma in ARP (ARPP) with regeneration-stimulating-potential, such as IGF1 and PRG4. Topical application of IGF1 or IGF1 + PRG4 to rat FTE wounds greatly promoted regenerative healing; particularly in the combination of IGF1 and PRG4 group. In summary, our findings convincingly demonstrate that the systemic factors from deer blood taken during ARP contain factors capable of inducing regenerative wound healing and that this effect is not species-specific. Because there are almost no restrictions on the supply of deer blood in ARP, our findings have laid the foundation for devising effective therapies for scar-less wound healing in the clinical setting.